ANALISIS KELAYAKAN DAN KEEFEKTIFAN MEDIA PEMBELAJARAN FLIPBOOK BERBASIS HEYZINE - Lailatul Mukarromah, Alfi; Nurveda Carreza , Arqoma; Dewi, Utari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the feasibility and effectiveness of hezine based flipbook learning media on marketing goods and services materials for tenth-grade TKJ students at SMK At-taufiqiyah.This reserch employed the Reserach and Development (R&D) method using the ADDIE development model,which consists of five stages:analyze,design,development, implementation, and evaluation, the research subjects consisted of 39 eleventh-grade TKJ students. data were collected through observation, documentation, material and media expert validation, student response questionaires, and learning outcome tests in the form of pretests and posttests.The learning media were developed using canva and published through the heyzine platform to produce an interactive digital flipbook that is easily accessible via smartphones and laptops.the media expert validation obtained a score of 87,37%,the material expert validation obtained a score 100%,and the instructional design expert validation obtaineda score of 98,67%,all of which catergorized as highly feasible.efectiveness test showed an improvement in studens learning outcomes,while the average pretest score increasing from 64,62% to 90,92%.in the posttest,and an N-gain score of 0,87 ,which falls into the high category.the findings indicate that the Heyzine-based flipbook learning media is highly feasible and effectivenees for teaching marketing goods and services materials.therefore,the Heyzine-based flipbook can be used an alternative learning medium to improve students’learning outcomes.